упростить 1. 19 cos^2 x - 9 + 19 sin^2 x

2. 17 cos^2 x - 5 + 17 sin^2 x

3. (sin^3 x - cos^3 x) / (1 + sinxcosx) +cosx - sinx

1

Ответы и объяснения

2010-11-29T15:04:48+00:00

1. 19 cos^2 x - 9 + 19 sin^2 x=19(cos^2(x)+sin^2(x))-9=19-9=10

2. 17 cos^2 x - 5 + 17 sin^2 x=17(cos^2(x)+sin^2(x))-5=17-5=12

3. (sin^3 x - cos^3 x) / (1 + sinxcosx) +cosx - sinx=

= [(sinx-cosx)(sin^2(x)+sinxcosx+cos^2(x))/(1+sinxcosx)]+cosx-sinx=

= [(sinx-cosx)(1+sinxcosx)]/(1+sinxcosx)]+cosx-sinx=sinx-cosx+cosx-sinx=0